The effects of clean and jerk rack position time on subsequent jerk kinetics - Rodriguez, M. R. (2019)
In the sport of Olympic weightlifting, athletes typically select their preferred rack position time (RPT) for the clean and jerk (CJ). Prior to this study, there has been a lack of scientific inquiry into the effects of RPT on jerk kinetics and overall CJ performance. Thus, the purpose of this study was to examine the effects of RPT during the CJ on subsequent jerk power, force, and velocity in trained Olympic weightlifters. Twenty (n=20) trained males participated in this crossover design study. Subjects completed four RPT condition: 4s, 8s, 12s, and self-selected RPT across two separate visits (2 RPT conditions per visit). During each RPT condition the CJ was performed using 80% of their pre-determined one repetition maximum. Kinetic measures were acquired during the jerk portion of the lift following the RPT using a linear position transducer. There was no main effect for condition (self-selected vs. 4s, vs. 8s, vs. 12s RPT) for peak power (p=0.37), average power (p=0.35), peak velocity (p=0.92), average velocity (p=0.78), or peak force (p=0.08). There was no significant interaction of relative strength and RPT condition for peak power (p=0.23), average power (p=0.86), peak velocity (p=0.52), average velocity (p=0.47), or peak force (p=0.05). Specifically, subjects with relative 1RM strength below the average (1.21 kg/kg) exhibited no difference in all dependent variables among the RPT conditions. Similarly, subjects with relative 1RM strength above the average demonstrated no difference in all dependent variables among each of the RPT conditions. There was also no significant interaction of limb lengths and RPT condition for all dependent variables. In conclusion, there was no effect of RPT whether pre-determined at varying timeframes or self-selected on subsequent jerk kinetics although trends indicated the lowest kinetic output during the jerk with 12s RPT and power and velocity maximized with 8s RPT. Also, peak force, on average, was greatest during the self-selected RPT which was less than 4s.